ALEXITHYMIA, MEN, AND THE DENIAL OF VULNERABILITY (PRÁXIS EM SAÚDE, 2025)
The word Alexithymia is Greek, meaning the absence of words for emotions, and it emerged in the 1970s with psychiatrist Peter Emanuel Sifneos. This condition may be related to neurobiological factors or childhood traumas. This is an exploratory and documentary review study, and it is also a cross-cutting topic that involves Social Psychology and Public Policies. It is justified by the sustained increase in cases of male suicide, violent deaths, and morbidity and mortality. The study sought to answer how culture and male invulnerability may be associated with Alexithymia. The central objective of this work is to analyze the relationship between Alexithymia and male risk behaviors. Among the theorists who addressed the subject, the following stand out: Carneiro, B.; Yoshida, E. (2009); Freire, L. (2010); Guardi, P. (2019); Lane, S. and Codo, W. (1989); Reid, C. (2015). To support the research, official data were collected from 2023 from the World Health Organization (WHO) and the National Public Security Information System (SINESP). Therefore, it is inferred that male behavior expresses in culture a point of intersection between what should not be said because one is a man and the difficulty of expressing oneself. Thus, avoidance of fear, or inability to recognize risks, puts him in danger, which is referred to as male ontological Alexithymia—a fact to be considered in clinical practice so that vulnerabilities are recognized and processed.
Keywords: Alexithymia; Masculinity; Vulnerability